Routledge handbook of international law and the humanities - Chalmers, Shane; Pahuja, Sundhya (London : Routledge, 2021)
"This handbook brings together 40 of the world's leading scholars and rising stars who study international law from disciplines in the humanities - from history to literature, philosophy to the visual arts - to showcase the distinctive contributions that this field has made to the study of international law over the past two decades. Outlining new ways of imagining, and doing, international law at a moment in time when original, critical thought and practice is more necessary than ever, this handbook will be essential for scholars, students and practitioners in international law, international relations, as well as in law and the humanities more generally"--
International law and the humanities in the 'anthropocene' / Kathleen Birrell and Julia Dehm -- Who, or what, is the human of international humanitarian law? / Matilda Arvidsson -- Automating authority : the human and automation in legal discourse on the meaningful human control of lethal autonomous weapons systems / Connal Parsley -- Rainbow family : machine listening, improvisation and access to justice in international family law / Sara Ramshaw -- In the name of the victim : representing victims in international criminal justiceMaria Elander -- A sovereignty that is 'useless to fascism' / Richard Joyce.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: mezinárodní právo -- sociální aspekty; humanitní vědy; mezinárodní právo soukromé; trestní řízení; lidská práva; mezinárodní právo humanitární; rodinné právo; trestní soudnictví; international law -- social aspects; humanities; private international law; criminal procedure; human rights; humanitarian law; family law; administration of criminal justice; e-knihy online; e-books online